Low velocity impact response of functionally graded carbon nanotube reinforced composite beams in thermal environment. (15th November 2015) - Jam, J.E.; Kiani, Y.
Abstract: Response of functionally graded carbon nanotube reinforced composite (FG-CNTRC) beam subjected to the action of an impacting mass is analyzed. Timoshenko beam theory is used to estimate the kinematics of the beam. Material properties of the fibers and polymeric matrix are assumed to be temperature dependent. Both uniform and functionally graded distribution of CNTs are taken into account. Material properties of the composite are obtained using a refined rule of mixture. Contact force between the impactor and the beam is obtained with the aid of the conventional Hertz law. The governing dynamic equations of the system, are obtained using the conventional polynomial Ritz method applied to the total energy of the system. The solution of the resulting equations is traced in time using the well-known Runge–Kutta method. After examining the validity of the present solution, parametric studies are conducted to examine the influences of thermal environment, volume fraction of the CNTs, distribution of CNTs, initial velocity of the impactor and the impactor mass. Numerical results reveal that as the volume fraction of CNTs increases in the beam, peak contact force increases and the contact time decreases. Furthermore, temperature rise results in higher contact time duration and lower peak contact force.